Assessing the potential and economic efficiency of reducing green house gas emission from organic domestic waste treatment technologies: A case study of Nam Son and Cau Dien disposal sites in Ha Noi - Minh, Thai Thi Thanh; Anh, Nguyen Trung; Lee, Joo Young; Dung, Bach Quang (VNU Journal of Science: Earth and Environmental Sciences, 2017)
The study focuses on assessing the potential and the efficiency of the economy with regard to reducing greenhouse gas (GHG) emissions from organic solid waste treatment technologies, including non-recovery landfill, landfill, and gas recovery for power generation (applied in Nam Son disposal site) and composting (applied in Cau Dien disposal site) in Hanoi. Research results illustrate that the treatment for one ton of organic domestic waste by landfill without gas recovery and landfill with gas recovery needs to cover losses about $14.2 USD and $0.9 USD respectively. While the application of composting technology makes a profit about $5.1 USD, composting has the potential to significantly reduce GHG emissions and to use the by-products after the process which can create profits to re-investment. Additionally, it is also in line with the plan of Hanoi People’s Committee for waste treatment in the future. However, the stepwise implementation of composting technology should start in 2030. Keywords Greenhouse gas emission reduction, organic solid waste, economic efficiency References [1] Sudokwon landfill site management corp. Converting waste resources into energy, landfill to dreampark. http://eng.me.go.kr/eng/web/index.do?menuId=54 [2] Tổng luận về công nghệ xử lí chất thải rắn của một số nước và ở Việt Nam (2017). Trung tâm Thông tin Khoa học và Công nghệ Quốc gia. [3] Võ Diệp Ngọc Khôi (2014). Nghiên cứu tính toán phát thải khí Mêtan từ BCL chất thải rắn Khánh Sơn Thành phố Đà Nẵng đến năm 2030. Luận văn thạc sĩ kỹ thuật. [4] Global Methane Intiative (2011). Landfill Methane: Reducing Emissions, Advancing Recovery and Use Opportunities. USEPA. [5] Nguyễn Võ Châu Ngân và cộng sự (2014). Tính toán phát thải khí Mê-tan từ rác thải sinh hoạt khu vực nội ô thành phố Cần Thơ. Tạp chí Khoa học Trường Đại học Cần Thơ, số 31 trang 99-105. [6] Phạm Thị Anh (2015). Sự phát sinh và phát thải khí BCL & phương pháp giảm thiểu. Trường Đại học Dân lập Văn Lang. [7] Nguyễn Văn Phước và cộng sự (2010). Công nghệ lên men Mêtan kết hợp với phát điện - giải pháp xử lý rác cho các đô thị lớn, góp phần kìm hãm biến đổi khí hậu. Tạp chí phát triển khoa học và công nghệ, tập 3 số M2 . [8] R. Pipatti và cộng sự (2006). Guidelines for national greenhouse gas inventories: reporting instructions, IPPC, Vol 5, Chapter 3. [9] H. F. Campbell, & R. P. Brown (2003). Benefit-cost analysis: financial and economic appraisal using spreadsheets. Cambridge University Press. [10] Haarlem et al (2003). A comparison of measurement methods to determine landfill methane emissions. This project was financed by the Dutch Ministery of Housing, Spatial Planning and Environment in the framework of the programme Reductie Overige Broeikasgassen 2000 (Reduction Other Greenhouse Gasses 2000). The programme is managed by Novem. [11] Heijo Sharff et al (2006). Applying guidance for methane emission estimation for landfill. Waste management, Vol 6, pp.417-429. [12] Nguyễn Thị Khánh Huyền và cộng sự (2015). Ứng dụng mô hình IPCC (2006) nhằm ước tính phát thải khí metan từ chất thải rắn sinh hoạt, tại thành phố Thủ dầu một, tỉnh Bình Dương. Tạp chí Khoa học Trường Đại học Cần Thơ, trang 183-192. [13] Laura Capelli et la (2014). Evaluation of landfill surface emissions. Chemical enginneering transactions. Vol. 40, pp. 187-192. [14] Đặng Thị Liên (2016). Đánh giá phát thải khí nhà kính metan (CH4) từ bãi chôn lấp chất thải hữu cơ: Nghiên cứu tại bãi rác Xuân Sơn, Sơn Tây, Hà Nội và đề xuất biện pháp giảm thiểu. Luận văn thạc sỹ biến đổi khí hậu. [15] G. P. Jenkins & A. C. Harberger 91997). Cost-Benefit Analysis of Investment Decisions. Boston, MA: Harvard Institute for International Development. [16] Uỷ ban Châu Âu (2008). Guidelines for the Cost-Benefit Analysis of Waste management projects. [17] Cục Khí tượng Thủy văn và Biến đổi khí hậu (2016). Nghiên cứu, xây dựng hệ số phát thải EF của lưới điện Việt Nam. [18] A. L. Marten & S. C. Newbold (2012). Estimating the social cost of non-CO2 GHG emissions: Methane and nitrous oxide, Energy Policy, 51(2012) 957-972. [19] Melissa Weitz et al (2017). Estimating National Landfill Methane Emissions: An Application of the 2006 Intergovernmental Panel on Climate Change Waste Model in Panama. Journal of the Air & Waste Management Association. Vol 50, pp.636-640. [20] Farideh Atabi et al (2014). Calculation of CH4 và CO2 emission rate in Kahrizak landfill site with Land GEM mathematical model. The 4th World Sustainability Forum. [21] Công ty TNHH một thành viên môi trường đô thị Hà Nội -URENCO (2009, 2015). Báo cáo hiện trạng công tác quản lí chất thải tại thành phố Hà Nội - Tính hình hoạt động của Khu Liên hiệp Xử lí Chất thải (LHXLCT) Nam Sơn. [22] Bogner J (2003). Global methane emission from landfill: New methodology and annual estimates 1980-1996. Global biogeochemical cycles, Vol 17, No. 2, pp.1-18. [23] Quyết định Phê duyệt Quy hoạch xử lý chất thải rắn thủ đô Hà Nội đến năm 2030, tầm nhìn đến năm 2050, Số 609/QĐ-TTg, ngày 25 tháng 4 năm 2014. [24] Trần Phương và cộng sự (2016). Nghiên cứu hiệu quả kinh tế trong giảm nhẹ KNK cho lĩnh quản lý chất thải. Đề tài nghiên cứu khoa học cấp Bộ. [25] Trịnh Ngọc Tuấn và cộng sự (2014). Đánh giá giảm phát thải khí nhà kính của phương pháp ủ so với chôn lấp chất thải rắn ở thành phố Huế. Tập 1, Số 1, Tạp chí Khoa học và Công nghệ, Trường Đại học Khoa học Tự nhiên.